2008
DOI: 10.2174/156652408784533779
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Microbiota and Probiotics in Stress-Induced Gastrointestinal Damage

Abstract: Stress has a major impact on gut physiology and may affect the clinical course of gastro-intestinal diseases. In this review, we focus on the interaction between commensal gut microbiota and intestinal mucosa during stress and discuss the possibilities to counteract the deleterious effects of stress with probiotics. Normally, commensal microbes and their hosts benefit from a symbiotic relationship. Stress does, however, reduce the number of Lactobacilli, while on the contrary, an increased growth, epithelial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
106
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(117 citation statements)
references
References 236 publications
1
106
0
6
Order By: Relevance
“…Although proper functioning of the GI system requires a community approach, some roles of specific bacteria in the maintenance of epithelial barrier integrity have been identified [67,[94][95][96][97][98]. For example, Bacteroides thetaiotaomicron promotes the upkeep of cadherin desmosomes, a juncture protein that links cells together [94] and inhibits NF-kB function [95]; several Lactobacillus strains stabilize tight junctions to preserve epithelial permeability [96,97]; Bacteroides fragilis aids in the correction of gut permeability [67], and; secreted bioactive factors from Bifidobacterium infantis enhance epithelial barrier function [98]. A recent and elegant study performed with gnotobiotic mice verified a direct relationship between the presence of gut microbiota and blood-brain barrier permeability [99].…”
Section: Epithelial and Endothelial Barrier Integritiesmentioning
confidence: 99%
“…Although proper functioning of the GI system requires a community approach, some roles of specific bacteria in the maintenance of epithelial barrier integrity have been identified [67,[94][95][96][97][98]. For example, Bacteroides thetaiotaomicron promotes the upkeep of cadherin desmosomes, a juncture protein that links cells together [94] and inhibits NF-kB function [95]; several Lactobacillus strains stabilize tight junctions to preserve epithelial permeability [96,97]; Bacteroides fragilis aids in the correction of gut permeability [67], and; secreted bioactive factors from Bifidobacterium infantis enhance epithelial barrier function [98]. A recent and elegant study performed with gnotobiotic mice verified a direct relationship between the presence of gut microbiota and blood-brain barrier permeability [99].…”
Section: Epithelial and Endothelial Barrier Integritiesmentioning
confidence: 99%
“…Additionally, we observed that the PP subjects were more likely to be overweight (Table I) than their age-matched counterparts in the control group, although their body weights were not up to the standard of obesity. There is strong evidence that chronic life stress directly impacts gastrointestinal function in animals and humans (62)(63)(64) and increases the activity of both the hypothalamic-pituitary-adrenal axis and the sympathoadrenal system (65). As emerging evidence demonstrates the influence of gut microbiota on the development, behavior, and function of CNS (66), it is increasingly important to understand the intricate relationship between CNS, gut microbiota, and metabolic phenotypes in the development of precocious puberty.…”
Section: Urinary Metabolites From Triptorelin and Derivatives-trip-mentioning
confidence: 99%
“…Podobnie, na wzmocnienie bariery jelitowej wpływają niektóre pałeczki Lactobacillus spp. (30). Aktywacja szlaku sygnałowego przez bakteryjny peptydoglikan za pośrednictwem TLR2 przyczynia się do podtrzymywania ścisłych połączeń i obniżonej apoptozy enterocytów, w konsekwencji do zachowania integracji nabłonka jelitowego.…”
Section: Mechanisms Of Maintenance Of Intestinal Homeostasis By Autocunclassified